Magnetizing Characteristics of Bridge Type Superconducting Fault Current Limiter (SFCL) with Simultaneous Quench Using Flux-Coupling - Seok-Cheol Ko; Tae-Hee Han; Sung-Hun Lim (Energies, 2020)
A bridge type superconducting fault current limiter (SFCL) with simultaneous quench using two high-temperature superconducting (HTSC) elements and two coils was fabricated to analyze the fault current limiting characteristics. Before and after the fault occurrence, the current limiting operation and the voltage waveforms of each device were compared according to the change of the input voltage. We also analyzed flux linkages and instantaneous powers of the bridge type SFCL with simultaneous quench using flux-coupling composed of HTSC elements with different critical currents. During the fault period, the magnetization power area and the flux linkage’s operating range variation due to the magnetizing current were compared with each other.